Relationship Of Family Support With Quality of Life (QOL) Stroke Occurrence - Hermawati Hamalding; Muharwati Muharwati (Promotif : Jurnal Kesehatan Masyarakat, 2017)
World Health Organization (WHO) states that the clinical signs that develop rapidly due to focal or global brain function disorders due to a blockage or rupture of blood vessels in the brain that lasted for 24 hours or more.This study aims to determine the Family Support Relationship With Quality of Life on Stroke Occurrence at Poly Nerve General Hospital of Makassar Hajj Area 2017. The research design was observational with cross sectional approach. Sample amounted to 54 by using simple random sampling technique. The result of the research was obtained by informational support with x2 count (4,352)> x2 table (3,841), emotional support p value (0,751)> 0,05, instrumental support with p value (0,346)> 0,05, award support with value x2 count (5,178)> x2 table (3,841). Based on the results of the study, the conclusion of this study found that there is a relationship of informational support and awards support, While emotional support and instrumental support is not associated with Quality of Life stroke incidence. This study suggests to families to provide more support to patients so as to improve the quality of life.Keywords           : Family Support and Quality of Life (QOL)